Internal Control System for Mexican Public Schools: The Case of An Elementary Public School in Querétaro, México - Ortiz, Ricardo; Álvarez, Brenda Liliana (Archives of Business Research, 2024)
Just like an onion, we must analyze corruption in layers. Firstly, where do people obtain values in order to participate in society? The answer is: at home, because that is where education begins. Parents are a strong role model and behavioral example for children, so, in order to let them play a more continuous role, they should participate in formal education by creating an organization that allows them to manage some school activities. Although regulation exists, the challenge arises when money is collected, because parents often don’t know basic accounting principles and mostly they only have basic reading and writing skills. There is no effective management of resources, opening the door to acts of corruption. This project is a transformational proposal to help public elementary school parents’ associations to be successful as an organization with higher standards of integrity. The final product is an internal system enabling better control of financial resources in an easy to learn and understand tool.